Asuhan Keperawatan pada Penderita Penyakit Jantung Koroner di Rumah Sakit Simpang Gumul Kediri - Wijaya Atmaja Kasuma; Supriandi Supriandi; Yuyun Christyanni; Rafi Farizki (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – Coronary heart disease is a familiar yagn. The disease that has earned the nickname as the number one killer is indeed suffered by quite a lot of people in the world and in Indonesia. East Java is one of the areas with the highest coronary heart disease rate in Indonesia. One of the hospitals in East Java that plans to provide a special ward for heart disease is Simpang Lima Gumul Hospital, Kediri Regency. Coronary heart disease patients must receive special nursing care because the potential for coronary heart morbidity is very high. Therefore, this study aims to provide knowledge related to nursing care for patients with coronary heart disease so that patients who avoid death from coronary heart disease can have a higher chance of survival. This research method is qualitative with an observation approach. The data used is a combination of primary data and secondary data that are mutually supportive and related. The results of the study show that coronary heart patients must carry out some nursing care and pain management. There are still many patients who do not understand coronary heart nursing care properly. In addition, pain management is also sometimes not well educated to patients or patient companions.